1992
DOI: 10.1002/mus.880150504
|View full text |Cite
|
Sign up to set email alerts
|

Human myoblast transplantation: Preliminary results of 4 cases

Abstract: Myoblasts from immunocompatible donors have been transplanted into the muscles (tibialis anterior, biceps brachii, and/or extensor carpi radialis longus) of 4 Duchenne patients in the advanced stages of the disease. Although no immunosuppressive treatment was used, none of the patients showed any clinical signs of rejection such as fever, redness, and inflammation. One patient transiently produced antibodies against the donor myoblasts as determined by cytofluorometric analysis. This patient and 2 others were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(107 citation statements)
references
References 39 publications
1
104
0
2
Order By: Relevance
“…54 The SV40 large T antigen and telomerase immortalized myoblasts have been described. 15 These cells were grown in MCDB 120 supplemented as described by Ham et al 55 without epidermal growth factor and fetuin, with or without 15% (v/v) decomplemented fetal bovine serum (FBS) (Gibco BRL, Burlington, ON, Canada).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…54 The SV40 large T antigen and telomerase immortalized myoblasts have been described. 15 These cells were grown in MCDB 120 supplemented as described by Ham et al 55 without epidermal growth factor and fetuin, with or without 15% (v/v) decomplemented fetal bovine serum (FBS) (Gibco BRL, Burlington, ON, Canada).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…14,15 Despite positive results in these small rodents, [16][17][18][19][20] clinical trials have presented limited success. [21][22][23][24][25][26][27][28][29] Improvements of injection and immunosuppression parameters have recently been achieved in primates 9,10,30 and translated to the human situation with encouraging, although localized success. 31 Nevertheless, one of the most important problems of heterologous MT remains the immune response raised by the recipient against donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…31 Nevertheless, one of the most important problems of heterologous MT remains the immune response raised by the recipient against donor cells. 22,29 This issue is completely avoided in the context of autologous MT, which has been successfully developed as an experimental treatment for postischemic heart failure or dilated cardiomyopathy, showing its feasibility, safety and its great clinical interest. [32][33][34][35][36] In some myopathic condition such as FSHD, characterized by a relatively localized muscle involvement, and the absence of therapeutic options, autologous MT could be considered as an alternative strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In the case of DMD, the only clinical trials performed to date involved healthy myoblast graft. [11][12][13][14][15][16][17][18] In these trials, which involved a total of 60 patients, the heterologous cells were obtained from healthy donors, either HLA compatible or incompatible; 16,18 one trial involved homozygous siblings. 19 An additional 150 patients were involved in further studies performed, 20 which however were controversial.…”
Section: Introductionmentioning
confidence: 99%
“…19 An additional 150 patients were involved in further studies performed, 20 which however were controversial. 21 Some of those clinical studies reported immune response as shown by detection of antibodies (Ab) against the engrafted cells, 13,18,19 even in the case of HLAcompatible patients, 16 and against dystrophin. 16,18 Some, but not all, of the patients tested displayed anti-dystrophin Ab as shown by Western blot techniques, which however were of low sensitivity.…”
Section: Introductionmentioning
confidence: 99%